Detection of Methicillin-Resistant Staphylococcus aureus in Clinical and Subclinical Mastitis in Ruminants and Studying the Effect of Novel Green Synthetized Nanoparticles as One of the Alternative Treatments - Abeer Mostafa Abdalhamed; Gamil Sayed Gamil Zeedan; Amany Ahmed Arafa; Eman Shafeek Ibrahim; Doaa Sedky; Amani Abdel nabey Hafez (Veterinary Medicine International)
Mastitis is an important disease in dairy animals worldwide. Methicillin-resistant Staphylococcus aureus (MRSA) is one of the most common causes of clinical and subclinical intramammary infections. In the current study, we isolated bacteria from 150 mastitic milk samples. Multiplex PCR was used to detect the methicillin resistance genes in S. aureus to detect the occurrence of MRSA isolates. Green synthesized titanium dioxide nanoparticles (TiO2 NPs) using aqueous leaf extracts of Artemisia herb Alba (A. herb Alba TiO2 NPs). The antibacterial efficacy of these nanoparticles was evaluated (in vitro and in vivo) against collected MRSA isolates using the disc diffusion method and SPF rats. Out of 150 mastitic milk samples, the frequency of S. aureus was 38 (25.3%), that of E. coli was 45 (30%), that of Klebsiella spp. Was 7 (4.7%), and that of Streptococcus spp. Was 11 (7.3%). Among 38 positive isolates of S. aureus, MRSA was 16 (42.1%) by antimicrobial sensitivity testing (AST) and 14 (38.8%) by multiplex PCR. The MRSA isolates were shown to have 100% resistance to penicillin and methicillin, 87.5% resistance to gentamicin, 50% resistance to cefoxitin and amoxicillin, and 75% resistance to ampicillin and ampicillin/sublactam with low resistance against erythromycin, ciprofloxacin, tetracycline, and levofloxacin by AST, respectively. A. herb Alba TiO2 NP formation was observed by changing the colour from white to dark green. The UV spectrum revealed absorbance peaks at 240–250 nm, and their sizes ranged from 42–66 nm and 11 to 45 nm by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). ‏A. herb Alba TiO2 NP suspensions were evaluated against MRSA, with the highest zone of inhibition (43 ± 0.45 mm) at a concentration of 40 μg/ml. Hematological parameters and histological examination after oral administration of 20 mg/kg of A. herb Alba TiO2 NPs indicated that A. herb Alba TiO2 NPs can be used as a new antimicrobial against resistant bacteria (MRSA) with consideration of the dose and methods of synthesis of plant-based compounds.